2011
DOI: 10.4236/epe.2011.33029
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Numerical Analysis of the Mechanical Erosion in Steam Turbine Blades. Part I

Abstract: The methodology of calculation of the velocity distribution for the stream frictionless and the drops in the flow line, on the basis of the frictionless, two-dimensional, stationary, transonic and homogenous flow is established. The knowledge of conditions that govern the low pressure section of steam turbines in the last stage to have an approximate movement of the droplets in the blade cascades and the accumulation of droplets on the stator blades, flowing through the steam, is presented. This study is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Depending on the operating condition and the backpressure of the turbine the wetness mass fraction is found to be in the range between 3-8%. The condensed water environment consists of very small droplets in the submicron range as well as coarse droplets of up to 100 μm in diameter [30,31]. Nevertheless, the small droplets in the range of 0.1 to 1 μm contribute most to the concentration of the condensed environment.…”
Section: Sample Volumementioning
confidence: 99%
“…Depending on the operating condition and the backpressure of the turbine the wetness mass fraction is found to be in the range between 3-8%. The condensed water environment consists of very small droplets in the submicron range as well as coarse droplets of up to 100 μm in diameter [30,31]. Nevertheless, the small droplets in the range of 0.1 to 1 μm contribute most to the concentration of the condensed environment.…”
Section: Sample Volumementioning
confidence: 99%
“…The experimental results showed that the model was accurate for predicting the erosion of catalyst. Moreover, similar studies have also focus on the important equipment components such as steam turbine nozzles [7][8][9] and rotor blades [10,11].…”
Section: Introductionmentioning
confidence: 99%